EFFECT OF REDUCED SALINITY ON THE INITIAL MORTALITY OF SPRAT, SPRATELLOIDES DELICATULUS (BENNETT), IN CAPTIVITY - Gopakumar, G; Mathew, C V (Indian Journal of Fisheries, 2011)
The effect of exposure to different concentrations of sea water on the initial mortality of Spratelloides delicatulus, the common tuna-live-bait fish of Lakshadweep, was experimented. The shock mortality of the fish due to stress of capture was found to be greatly! reduced by introducing them at once in 50% sea water. However, the aggregate mortality from the time of capture to the end of the second day was least among the fish exposed to 75% sea water, being about three-fourth of the mortality in 100% sea water.